Functionalization of Natural Compounds to Enhance the Bioactivity of Zerumbone in Cancer Chemotherapy - Truong, Ngoc Hung; Le, Duc Anh; Vu, Thi Ha; Cam, Thi Inh; Do, Huu Nghi; Nguyen, Manh Cuong; Tran, Khac Vu; Tran, Hanh Nguyen; Pham, Van Chung; Luu, Van Chinh (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
The alkylation reaction was employed to conjugate zerumbone with 3-substituted quinazolinone-4(3H)-ones and quinolines, resulting in the synthesis of 11 novel conjugates. These conjugates were thoroughly characterized using 1D-, 2D-NMR, and HRMS spectral data. Their enhanced bioactivity was evaluated through anti-inflammatory assays, specifically by inhibiting NO production in RAW 267.4 cells. Additionally, their cytotoxic activity was assessed against three human cancer cell lines: HepG2, SK-LU-1, and MCF-7. The results demonstrated that all 11 conjugates exhibited significantly potent cytotoxic activity, with IC50 values ranging from 1.01 to 9.86 µg/mL, surpassing the efficacy of the parent compound zerumbone. Furthermore, in silico studies, including EGFR inhibitory activity through docking and molecular dynamics simulations, were conducted to identify the most potent compounds. These studies highlighted the key interactions of zerumbone derivatives 16a-k with critical amino acids in the active site of the EGFR (PDB ID 4HJO) protein.